Cover Feature: Direct Catalytic Conversion of Furfural to Furan‐derived Amines in the Presence of Ru‐based Catalyst (ChemSusChem 7/2020). Issue 7 (6th April 2020) - Jiang, Shi; Ramdani, Wahiba; Muller, Eric; Ma, Changru; Pera‐Titus, Marc; Jerôme, François; De Oliveira Vigiera, Karine
Abstract : The Cover Feature shows a simple and efficient preparation of furan‐derived amines in a one‐reactor tandem concept using bio‐derived ketones, NH3 as a nitrogen source, molecular H2 as a reducing agent, and commercially available Ru/C as catalyst. More information can be found in the Communication by S. Jiang et al. on page 1699 in Issue 7, 2020 (DOI: 10.1002/cssc.202000003 ).